Role of technology entrepreneurship in the development of innovativeness of small and medium-sized enterprises = Rola przedsiębiorczości technologicznej w rozwoju innowacyjności małych i średnich przedsiębiorstw - Matejun, Marek (Zielona Góra: Faculty of Economics and Management Press)
Technology entrepreneurship is an interesting concept for transforming the potential of the scientific and research and development fields (including a wider impact of the so-called business environment sphere) into innovative products and services. In consequence, it might become a key factor in building the innovation potential of modern enterprises, especially SME sector enterprises, which due to their resource shortages have limited ability to carry out independent research and development operations.
Keywords: przedsiębiorczość technologiczna; zarządzanie innowacjami; małe i średnie przedsiębiorstwa; technology entrepreneurship; innovation management; small and medium enterprises (SME)